2015
DOI: 10.1177/1933719115570899
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic Hormone and PI3K/Akt Inhibition Reduce eNOS Phosphorylation and Increase Cortisol Biosynthesis in Long-Term Hypoxic Ovine Fetal Adrenal Cortical Cells

Abstract: This study was designed to determine the role of the MEK/ERK1/2 and PI3K/Akt pathways in cortisol production and endothelial nitric oxide synthase (eNOS) phosphorylation (peNOS) in the ovine fetal adrenal in response to long-term hypoxia (LTH). Pregnant ewes were maintained at high altitude (3820 m) for the last 100 days of gestation (dGa). At 138 to 142 dGa, fetal adrenal cortical cells (FACs) were collected from LTH and age-matched normoxic fetuses. Cortisol production and peNOS were measured in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Subsequent studies by Monau et al (110) showed that NO reduced ACTH-mediated cortisol production in LTH fetal adrenocortical cells (FACs) in vitro, whereas inhibition of NOS activity increased cortisol production in LTH cells, with no effect on normoxic cells. Furthermore, ACTH reduced eNOS activation via phosphorylation in LTH FACs (123) and NO-dependent inhibition of ACTH-induced cortisol production, which further supports the role of NO in regulating cortisol production in the LTH fetal adrenal (171). This may be possible by NO competing with the oxygen-binding site of CYP11A1 and CYP17 (74,170), disrupting the heme-oxygen complex attack by the enzyme on the steroid substrate.…”
Section: Chronic Hypoxiamentioning
confidence: 65%
“…Subsequent studies by Monau et al (110) showed that NO reduced ACTH-mediated cortisol production in LTH fetal adrenocortical cells (FACs) in vitro, whereas inhibition of NOS activity increased cortisol production in LTH cells, with no effect on normoxic cells. Furthermore, ACTH reduced eNOS activation via phosphorylation in LTH FACs (123) and NO-dependent inhibition of ACTH-induced cortisol production, which further supports the role of NO in regulating cortisol production in the LTH fetal adrenal (171). This may be possible by NO competing with the oxygen-binding site of CYP11A1 and CYP17 (74,170), disrupting the heme-oxygen complex attack by the enzyme on the steroid substrate.…”
Section: Chronic Hypoxiamentioning
confidence: 65%
“…In addition, cortisol may increase Bovine endometrial epithelial cells(BEECs) proliferation by raising the production of certain growth factors and activating the Wnt/-catenin and PI3K/AKT signalling pathways (30). PI3K/Akt inhibition decreases eNOS phosphorylation and boosts cortisol production in chronically hypoxic foetal sheep adrenal cortical cells (31). Therefore, we speculate that cortisol may stimulate adrenal gland proliferation via the aforementioned pathways.PI3K/Akt pathway may promote the secretion of cortisol by adrenal cortical cells.…”
Section: Discussionmentioning
confidence: 94%
“…Once phosphorylated, Akt, the p65 subunit of NF-κB, translocates to the cell nucleus where it stimulates COX-2 gene transcription. 64 However, under normal conditions it is regulated by members of the mitogen-activated protein kinase (MAPK) family. Experimental studies have shown that activation of COX-2 induces the synthesis alpha factor, IL-6, and TNF-alpha, which are molecules that promote NO synthesis in macrophages and fibroblasts.…”
Section: No and Activation Of Cox-2mentioning
confidence: 99%